MICROSCOPIC AND DEMOGRAPHIC PROFILE OF SEXUALLY TRANSMITTED DISEASES AT A TERTIARY CARE CENTRE OF CENTRAL INDIA - GUPTA, ABHA; GUPTA, AMIT; SARASWAT, ASHISH; MEHTA, ABHISHEK (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: To find out the prevalence of sexually transmitted diseases (STDS) among the patients attending the tertiary care center through microscopic screening. Methods: This Cross Sectional study was conducted from April 2018 to December 2019 wherein 500 samples were collected from patients attending the STD clinic of Skin and VD-OPD, and integrated counseling and testing center (ICTC), having cervical or urethral discharge along with signs and symptoms of sexually transmitted infections (STI) and were screened microscopically for the same. Results: This study reported only 2 cases suggestive of N. gonorrhoeae on microscopy, wherein the Gram-stained smear showed the presence of a particular arrangement of Gram-negative coffee bean shape cocci, both intracellular and extracellular, and plenty of pus cells. In Direct Microscopy findings, 49.2% of samples showed normal flora, 20.4% Gram-positive cocci, 15.8% Gram-negative cocci, 4% Clue cells, 13.8% with mixed flora, 3% Budding yeast-like cells and 0.4% showed Gram-negative cocci. Conclusion: Such studies involving the laboratory and demographic data should be conducted regularly, which can help in estimating the disease burden, strengthening the diagnostic capacity, and formulating the requisite strategy for tackling this problem through a syndromic approach.